Perlindungan Hukum Terhadap Tindak Pidana Anak Sebagai Pelaku Kasus Pelanggaran Lalu Lintas Dihubungkan Dengan Undang-Undang No. 35 Tahun 2014 Tentang Perlindungan Anak - Usep Lala Sopandi (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2018)
Transportation in Indonesia is experiencing a very rapid development in the city or in the village. This development not only gives a positive impact but the negative impact of one of the many cases of traffic violations. The author identifies the issues to be studied as follows: What is the protection of children in the criminal justice system in Indonesia and how the implementation of legal protection against criminal offenses as perpetrators of cases of traffic violations is related to Law no. 35 Year 2014 on Child Protection? Approach method used is juridical-normative approach, that is through literature study. The data are analyzed qualitatively-normatively. The results showed that in January to May 2017, students were included in the first order of most perpetrators of traffic violation cases. In conclusion, the crime against children committing traffic violations based on Law No. 35 years 2014 About Child Protection, for sanctions can Subject to criminal sanctions and action sanctions. Its application should be distinguished by sanctions against adults.